Criminal major acts - "Arora, C. P." (Allahabad, 2019)
This book cover following topics The code of criminal procedure, 1973. The Indian penal code, 1860. The Indian evidence act, 1872. The protection of children from sexual offences act and rules.
Keywords: Criminal law-India